Review of spatial and inter-annual changes in the zooplankton community structure in the western Arctic Ocean during summers of 2008–2017. (July 2020) - Abe, Yoshiyuki; Matsuno, Kohei; Fujiwara, Amane; Yamaguchi, Atsushi
Highlights: Spatial and inter-annual changes of zooplankton community structure in the western Arctic Ocean were studied based on long time-series observations. Horizontal distribution was divided into four groups by cluster analysis. In statistical models, the relationship between abundant copepod species and freshening seawater was revealed in the Basin region. New-shelf assemblage, with low abundance and low species diversity, occurred in 2012, 2013, 2015 and 2017 when the melting sea ice was significantly earlier than the other years. Abstract: Reduction in summer sea ice coverage has recently been observed in the western Arctic Ocean. Changes in the coverage and timing of sea ice retreat are expected to have a great impact on the marine ecosystem. In this study, we evaluated inter-annual changes in the spatial distribution of zooplankton communities in the western Arctic Ocean, during the summers of 2008, 2010, 2012–2017. A total of 339 casts were conducted to collect zooplankton by vertical hauls at 22–63 stations per year in the western Arctic Ocean, between August 26 and October 13, 2008, 2010, 2012–2017. Based on cluster analysis, four zooplankton communities (basin, slope, shelf, and new-shelf) were identified. Horizontal distribution of the zooplankton communities corresponded with the depth of the sea floor. No significant interannual variability in zooplankton and copepod abundance was observed in the Canada basin; however, a decline in the abundance of dominant copepods associated with an enhanced freshening of seawater was suggested by a General Linear Model analysis. The shelf assemblage was characterized by a high abundance of Pacific species that was predicted by the length of the open water period. The new-shelf assemblage, located between the shelf and the slope, showed low species diversity and abundance and was observed only in 2012, 2015, 2016 and 2017 when the melting day of sea ice was significantly earlier than in the other years. Our study indicates that different changes in each region can be expected in response to the possible environmental changes in the Pacific Arctic.